Mass-imbalanced three-body systems in two dimensions - Bellotti, F. F.; Frederico, T.; Yamashita, Marcelo Takeshi [UNESP]; Fedorov, D. V.; Jensen, A. S.; Zinner, N. T. (IOP Publishing, 2013)
We consider three-body systems in two dimensions with zero-range interactions for general masses and interaction strengths. The momentum-space Schrödinger equation is solved numerically and in the Born-Oppenheimer (BO) approximation. The BO expression is derived using separable potentials and yields a concise adiabatic potential between the two heavy particles. The BO potential is Coulomb-like and exponentially decreasing at small and large distances, respectively. While we find similar qualitative features to previous studies, we find important quantitative differences. Our results demonstrate that mass-imbalanced systems that are accessible in the field of ultracold atomic gases can have a rich three-body bound state spectrum in two-dimensional geometries. Small light-heavy mass ratios increase the number of bound states. For 87Rb-87Rb-6Li and 133Cs- 133Cs-6Li we find respectively three and four bound states. © 2013 IOP Publishing Ltd.
Keywords: Adiabatic potentials; Born-Oppenheimer approximation; Bound state; Bound-state spectrum; Dinger equation; Heavy particles; Interaction strength; Mass ratio; Qualitative features; Separable potential; Three body; Three-body systems; Two-dimension; Two-dimensional geometry; Ultracold atomic gas; Zero range interaction; Lithium; Rubidium; Cesium